2021
DOI: 10.1038/s41598-021-03031-2
|View full text |Cite
|
Sign up to set email alerts
|

A success targeted nano delivery to lung cancer cells with multi-walled carbon nanotubes conjugated to bromocriptine

Abstract: In this research, a new nano drug-based multi-walled carbon nanotubes (MWCNTs) was prepared and evaluated qualitatively. Bromocriptine (BRC) was conjugated to functionalized carbon nanotubes. Then, the CHNS, FT-IR, SEM, and RAMAN tests for characterization of the conjugated drug were done. The nanofluid-containing nano-drug was evaluated on lung cancer cells (A549 & QU-DB) and MRC5 by MTT and flow cytometry tests. Then, the gene expression studies of dopamine receptor genes were done before and after nano-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 49 publications
(56 reference statements)
0
8
0
Order By: Relevance
“… 64 Future investigations of nanotechnology-based CS formulations in our experimental systems of macrophage polarization and LM biosynthesis might reveal if cytotoxicity and SPM-impairing effects may be circumvented. Indeed, drug delivery by nanofluids improved the efficacy of isoniazid 65 or of bromocriptine, 66 and encapsulation of a cytotoxic indirubin derivative into polymer-based nanoparticles reduced its detrimental impact on monocyte viability. 67 …”
Section: Discussionmentioning
confidence: 99%
“… 64 Future investigations of nanotechnology-based CS formulations in our experimental systems of macrophage polarization and LM biosynthesis might reveal if cytotoxicity and SPM-impairing effects may be circumvented. Indeed, drug delivery by nanofluids improved the efficacy of isoniazid 65 or of bromocriptine, 66 and encapsulation of a cytotoxic indirubin derivative into polymer-based nanoparticles reduced its detrimental impact on monocyte viability. 67 …”
Section: Discussionmentioning
confidence: 99%
“…Protein expression studies revealed that the proapoptotic protein Bax was upregulated, whereas the antiapoptotic protein Bcl-2 was downregulated in CNT-treated A549 cells compared with MRC5 cells treated with CNTs. 25 Similarly, MWCNTs functionalized with naringenin possessed an average diameter of 9.6 ± 1.4 nm and released naringenin effectively at pH 7.4 (83.5%) compared with pH 5.5 (60.8%) after 9 h compared with relatively smaller durations. The naringenin-functionalized CNTs presented limited cytotoxic effects on normal hFB fibroblasts compared with A549 cells.…”
Section: Cytotoxic Effects Of Drug-loaded Cnts On Nsclc Cells In Vitromentioning
confidence: 93%
“… 1. Bromocriptine Diameter of 25 to 40 nm, lengths ~ 500 nm A549, 49.20 μg/mL Upregulation of dopamine receptors DRD2 and DRD4, pro-apoptotic Bax and downregulation of anti-apoptotic Bcl-2 [ 25 ] 2. Naringenin Diameter of 9.6 ± 1.4 nm A549, 82.6 ± 7.3 µg/mL - [ 26 ] 3.…”
Section: Cytotoxic Effects Of Drug-loaded Cnts On Nsclc Cells In Vitromentioning
confidence: 99%
“…Lung cancer is one of the most prevalent cancers and the leading cause of death worldwide. n this study, a specific agonist of DRDs, BRC was delivered to lung cancer cells with MWCNTs and showed a significant anti-proliferative effect on cancer cells and low toxicity on normal lung cells [18]. Furthermore, one of these fundamental variables is the blood glucose level of a diabetic person.…”
Section: -Application Of Carbon Nanotubes In Medicine Filedmentioning
confidence: 95%